Réponses

Meilleure réponse !
2014-04-11T21:27:16+02:00
Bonsoir

45)

g = 3√8 - (5√8 +1) = 6√2 - 10√2 + 1 = 1 - 4√2
h) = (√10 +3) - ( 3 - 4√10) = √10 +3 - 3 + 4√10 = 5√10
i ) 6√3 - (3 + √12) = 6√3 -3-2√3 = -3 +4√3
j) (4 -√32) - (√50 -7) = 4 -4√2 - 5√2 -7 = -3 -9√2

46)
k) (√5 +4 )(3√5 -2) = 3√25 -2√5 + 12√5 - 8 = 15 - 2√5 + 12√5 - 8 = 7 +10√5
l)(3√2 +1)(3√2 -1) = 18 -1 = 17
m) (7√3 -2)(√3 +3) = 7√9 +21√3 -2√3 -6 = 21 + 21√3 -2√3 - 6 = 15 +19√3
n) (√11 -1) (2√11 -5) = 2√121 - 5√11 - 2√11 +5 = 22 - 5√11 - 2√11 +5 = 27 -7√11

47)
a) (√2 +1)(√2 -1) = (√2)² - 1² = 2 -1 = 1
b)5√27 +√75 = 15√3 + 5√3 = 20√3